Functional evaluation of Olympic competitors practicing boxing using the FMS - Kuzma, D.; Gorka, D.; Suszynski, K.; Dabrowska-Galas, M.; Dura-Nowaczyk, G.; Toborek, L. (Archives of Budo Conference Proceedings, 2015)
Background and Study Aim: Problem of postural stability, balance and motor function deregulation in fighting sports as boxing is well known. In this study we conducted boxers motor analysis, which could help do reduce the occurrence of injury and overloading of the movement Among the competitors. The aim of this study was clinical assessment of motor function in competitors and verification, whether training experience or other factors has an impact on the results of functional tests. Material and Methods: Address 32 fighters study, two groups of age. The average age of the players from Group 1 was 14 ± 0.94, while in group 2: 24 ± 1.78 years. The research tool was a functional traffic system (FMS) - Test is used to make international assessment of functional mobility, which includes 7 Different tests evaluated on a scale Bu 0-3. The results were statistically analyzed. Results: Research results showed that participants with greater training experience (11 ± 1.62) received fewer points in each FMS test, which indicated a decreased mobility of the shoulder girdle. Conclusions: Longer training experience will contribute boxers do to reduce the mobility of the shoulder girdle, while a positive effect on the length of the sciatic-tibial muscles.